Implementasi Pembiayaan Murabahah di Perbankan Syariah: Perspektif Undang-Undang No. 21 Tahun 2008 dan Maqâsid Al-Syarî’ah - M.Reza Saputra; Rian Wulandari (Khulasah : Islamic Studies Journal, 2026)
Murabahah has become a flagship product in Islamic banking in Indonesia and internationally, as evidenced by data from Bank Indonesia in 2023, which shows murabahah financing reaching IDR 380 trillion or 30.91% of total Islamic banking financing. The popularity of murabahah is supported by its fiqh scheme, which is considered to have low risk, transparency in prices and costs, fairness in payments, and compliance with sharia principles. However, the implementation of murabahah financing faces various challenges, including gaps in legal interpretation, regulatory inconsistencies, and a lack of understanding and education regarding the principles of maqâsid al-syarî’ah. This research uses normative legal methods to evaluate the effectiveness of murabahah implementation within the framework of Law No. 21 of 2008 and the principles of maqâsid al-syarî’ah. Through qualitative analysis of primary and secondary data, this research provides recommendations for improving legal interpretation, enhancing coordination between institutions, and educating the public to improve the quality and compliance with Sharia principles in murabahah financing.